SERVICE QUALITY AND BRAND REPURCHASE OF ELECTRONIC DEVICES: THE ROLE OF CUSTOMER SATISFACTION AND SHOPPING INVOLVEMENT AS MEDIATORS - Leecharoen, Benjawan; Boonyoung, Yingcharoen; Siangchokyoo, Nontavat (Asian Administration and Management Review, 2023)
The objectives of this research were: 1) to investigate the influence of service quality on the repurchase of an electronic device brand in the consumer market; and 2) to investigate how customer satisfaction and shopping involvement mediate the relationship between service quality and the repurchase of an electronic device brand. This research focuses on customer repurchase behavior for the same brand in the Thai electronics industry. Using a quantitative research method, purposive sampling was used to collect 388 samples from an electronic device retailer in Bangkok, Thailand. The self-administered questionnaire was a tool to collect aggregated data. The statistical selection then employed was the structural equation model. The results of the statistical tests supported the research hypothesis. This research found that the quality of service has a direct influence on the repurchase behavior of electronic devices from the same brand in Bangkok's consumer district. Indirectly, the quality of the service influences repeats purchase behavior via customer satisfaction and shopping involvement. In other words, if a business wants customers to return, the quality of its services must increase both customer satisfaction and shopping involvement in order to achieve a high return rate.